(untitled) (International Journal of Medical and Surgical Sciences, 2015)
In identification, odontometry is one of the techniques used since human beings have measurable characteristics such as height, and it is of great importance for the identification of skeletonized remains. The main objective of this study was estimating the actual height estimated according to method Carrea from the mesial distal diameters of the central and lateral incisors and lower canines in adolescents of both sexes. The study was conducted on 200 subjects, with actual height taken by the measuring board and subsequent impressions made of their lower jaw to work on models obtained. These were were assigned a code according to which we worked estimation by applying the Carrea formula, and then determined whether the estimation of the estimated actual height had some variation By examining 200 cases of both it sexes was determined that the actual height of the estimated height differed 0.005 variance, this means that Carrea method is effective for our population.